?ESSENTIAL OILS OF THE FAMILY GRAMINEAE WITH ANTIBACTERIAL ACTIVITY Part 2. The Antibacterial Activity Of A Local Variety Of Cymbopogan Citratus Oil And Its Dependence On The Duration Of Storage - SYED, MEENA; QAMAR, SHADAB; RIAZ, M.; CHAlJDHARY, M. (Biological Sciences - PJSIR, 1995)
ESSENTIAL OILS OF THE FAMILY GRAMINEAE WITH ANTIBACTERIAL ACTIVITY Part 2. The Antibacterial Activity Of A Local Variety Of Cymbopogan Citratus Oil And Its Dependence On The Duration Of Storage